Scalar-based direct algorithm mapping FPLD implementation of a Kalman filter - Salcic, Z.; Chung-Ruey Lee (IEEE transactions on aerospace and electronic systems, 2000)
A methodology of the scalar-based direct algorithm mapping (SBDAM) is defined and presented. The methodology uses direct mapping of the arithmetic expressions on to a field-programmable logic device (FPLD). A Kalman filter used in multiple target tracking (MTT) applications has been implemented in FPLD via SBDAM and via the other matrix-based systolic algorithm engineering (MBSAE) approach. The comparison between SBDAM and MBSAE drawn from this example is given in terms of various performance measures such as speed of the resulting circuit, required space (resource) requirements, ease of development, and others.